2020
DOI: 10.1002/cbf.3487
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 attenuates rat hepatocarcinogenesis via the reduction of CD59 expression and phospholipase D activity

Abstract: The current study aimed to test the profile of serum lipids, phospholipase D (PLD) activity, and CD59 expression pattern in rat hepatocellular carcinoma (HCC) after therapeutic treatment with Coenzyme Q10 (CoQ10). Three rat groups were allocated as normal control, untreated HCC, and treated HCC (HCC + CoQ10). The levels of serum α-fetoprotein (AFP) and tumour necrosis factor (TNF)-α were assessed using enzyme-linked immunosorbent assay (ELISA), while proliferating cell nuclear antigen (PCNA) was detected using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Coenzyme Q 10 treatment at a dose of 0.4mg/kg thrice a week for 2 weeks inhibited cell proliferation and histological alteration of liver [ 48 ]. Coenzyme Q 10 treatment increased lipids and cleaved caspase 3 and decreased TNF-α, AFP, Bcl-2, SRB1, phospholipase D (PLD) activity, and CD59.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coenzyme Q 10 treatment at a dose of 0.4mg/kg thrice a week for 2 weeks inhibited cell proliferation and histological alteration of liver [ 48 ]. Coenzyme Q 10 treatment increased lipids and cleaved caspase 3 and decreased TNF-α, AFP, Bcl-2, SRB1, phospholipase D (PLD) activity, and CD59.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies using rats were performed on Wistar rats and were confirmed by mechanisms such as SOD (3), ALP (3), c-caspase-3 (3) and NF-κB (3), p53, and Bax (2). Some reports lacked the source of the compound [ 42 , 43 , 44 , 47 , 48 ], and some studies lacked the classifications of the compound [ 43 ]. Meanwhile, some other studies presented both in vivo and in vitro experiments [ 41 , 44 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, the administration of CoQ10 produced a direct effect on the growth of cancer cells, without a clear mechanism of action. Abdel-Latif et al [67] showed that CoQ10 administration protected against the development of hepatocellular carcinoma in rats, via a reduction in CD59 glycoprotein expression and phospholipase D (PLD) activity. Treatment with CoQ10 (25 mg/rat) improved the survival of Yoshida-sarcoma-implanted rats [68].…”
Section: Studies In Animal Modelsmentioning
confidence: 99%
“…Abdel-Latif et al. showed increased mRNA and protein expressions of CD59 in a DEN-induced rat model of HCC that promoted enhanced tumor growth ( 161 ). In rats with HCC, increased levels of serum CD59 were not linked to phospholipase D (PLD)-dependent cleavage of CD59 ( 162 ) but rather to inflammation driven shedding from membrane lipid rafts ( 163 , 164 ).…”
Section: Complement Proteins In Hccmentioning
confidence: 99%